2022
DOI: 10.3390/ijms232112870
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Piezo1 Increases Na,K-ATPase-Mediated Ion Transport in Mouse Lens

Abstract: Lens ion homeostasis depends on Na,K-ATPase and NKCC1. TRPV4 and TRPV1 channels, which are mechanosensitive, play important roles in mechanisms that regulate the activity of these transporters. Here, we examined another mechanosensitive channel, piezo1, which is also expressed in the lens. The purpose of the study was to examine piezo1 function. Recognizing that activation of TRPV4 and TRPV1 causes changes in lens ion transport mechanisms, we carried out studies to determine whether piezo1 activation changes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Piezo1 can also activate the protein kinase pathway and further regulate the activity of multiple cell signaling pathways (Blythe et al, 2019;Chen S. et al, 2022;Wang et al, 2022). In addition, Piezo1 can also regulate the activity of Na, and K-ATPase, further affecting intracellular ion balance and cell membrane stability (Shahidullah et al, 2022;Hirata et al, 2023). Recently, Shahidullah M and his colleagues studied the relationship between Piezo1 and Na, K-ATPase-mediated ion transport in mouse crystals.…”
Section: Structure and Characteristics Of Piezo1mentioning
confidence: 99%
See 1 more Smart Citation
“…Piezo1 can also activate the protein kinase pathway and further regulate the activity of multiple cell signaling pathways (Blythe et al, 2019;Chen S. et al, 2022;Wang et al, 2022). In addition, Piezo1 can also regulate the activity of Na, and K-ATPase, further affecting intracellular ion balance and cell membrane stability (Shahidullah et al, 2022;Hirata et al, 2023). Recently, Shahidullah M and his colleagues studied the relationship between Piezo1 and Na, K-ATPase-mediated ion transport in mouse crystals.…”
Section: Structure and Characteristics Of Piezo1mentioning
confidence: 99%
“…Recently, Shahidullah M and his colleagues studied the relationship between Piezo1 and Na, K-ATPase-mediated ion transport in mouse crystals. They found that after activation of Piezo1, Na, K-ATPase in cells will be affected (Shahidullah et al, 2022).…”
Section: Structure and Characteristics Of Piezo1mentioning
confidence: 99%
“…Immunolocalization studies were carried out on intact ciliary body (CB) of porcine eye paraffin sections using an approach described earlier [ 34 , 35 ]. Porcine CBs were fixed in 10% neutral buffered formalin (NBF) for 24 h at 2–4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Piezo1 activates integrin-FAK signaling, regulates ECM and reinforces tissue stiffness to promote glioma aggression, while deleting Piezo1 inhibits tumor aggression and prolongs survival [ 153 ]. At present, only a few Piezo1 inhibitors (GsMTx4, ruthenium red, Dooku1, gadolinium) have been reported in preclinical studies and no agents are engaged in clinical trials [ 56 , 154 156 ]. The role of Piezo1 inhibitors in tumors is still in the initial stage, and with more in-depth research in the future, the development of drugs targeting Piezo1 may be of great value.…”
Section: Drugs Targeting Matrix Stiffness For Tumor Therapymentioning
confidence: 99%